2008
DOI: 10.1177/1010539508329207
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Age at First Birth in Rural Areas of Bangladesh

Abstract: The age at first birth is very low under existing rural sociocultural settings in Bangladesh. This study examined the socioeconomic and cultural determinants of age at first birth. The study subjects were married women aged 15 to 29 years in 2 rural areas that were identified through a multistage sampling technique. To collect the relevant information, a semistructured interviewer schedule was applied to the eligible women. This study found that 72.8% women gave first birth at <20 years of age with mean age at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
5
12
1
Order By: Relevance
“…While it reduces the rate of maternal and child morbidity and mortality on one hand, especially in Nigeria where the maternal mortality ratio (MMR) and infant mortality ratio (IMR) are above African Average [12]. On the other hand, delayed child bearing reduces fertility thereby, curtailing excessive population growth and improves standard of living among families through education and career development [6, 11, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it reduces the rate of maternal and child morbidity and mortality on one hand, especially in Nigeria where the maternal mortality ratio (MMR) and infant mortality ratio (IMR) are above African Average [12]. On the other hand, delayed child bearing reduces fertility thereby, curtailing excessive population growth and improves standard of living among families through education and career development [6, 11, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…The family factors are made up of socio-economic background characteristics such as, education of parents, place of residence, geographical region of birth, religion, social status, employment status, etcetera. The societal factors include norms practices, peer pressures, women’s liberation and acceptance of cohabitation [6, 7, 11, 1317].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in our study, disparity was seen between the levels of paternal and maternal education; a higher percentage of fathers had received college education; in contrast, a higher percentage of mothers had been educated less than nine years. We did not document the age at which the females in our study had gotten married but, the majority of mothers in our study were above 21 years of age in contrast to those in some developing countries, notably rural Bangladesh, where > 72% of first-time mothers were < 20 years of age (9). In our study, it was found that the mothers in the group, who had been educated for > 9 years were younger and more females in this group had two or more children, in contrast to the higher educated females, who, despite being older, had given birth to only one child.…”
Section: Discussionmentioning
confidence: 59%
“…Other studies have also shown that less educated females enter marriage earlier than educated individuals, start having children sooner, and also have more children, with the reverse being true for highly educated females (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%